Will The Israeli-Palestinian Two State Solution and Garuda Troops stop Gaza Genocide? - Murry Darmoko Moersidin (Indonesian Red Crescent Humanitarian Journal, 2026)
The Gaza genocide can only be stopped with a two-state solution and the Garuda Troops. This research uses qualitative methods sourced from reliable documents and news media, as well as an approach based on the Sociology of International Law. Two research questions are formulated: What is the role of Indonesian foreign policy in realizing the Israeli-Palestinian Two-State Solution? Is the Garuda Troop capable of stopping the Gaza genocide? The results of the study: first, the role of Indonesian foreign policy has an impact on the realization of the Israeli-Palestinian two-state solution. Second, the experience of the Garuda Troops in Lebanon and Congo has successfully maintained peace. The pros and cons of recognizing Israel and the Garuda Troops joining in resolving the Gaza genocide are discussed. The pro-genocide side wants the genocide to end along with the recognition of an independent Palestine by recognizing Israel as a state for historical reasons and international law. The contra-party side expresses a stance similar to that adopted by Hamas, which is to reject all options because it believes that all land occupied by Israel belongs to Palestine. Two conclusions, first, the two-state solution can be realized if the genocide can be stopped by proving the opening of diplomacy between Israel and Indonesia. Second, the Garuda experience in achieving peace.